Distanciamiento de siembra y su influencia en las características agronómicas y rendimiento de Capsicum annuum L. "pimiento", Zungarococha - Loreto. 2019 - Jimenez Vargas, Isabel (2022)
The experiment “Planting spacing and its influence on the agronomic characteristics and yield of Capsicum annuum L. “pepper”, Zungarococha-Loreto. 2019”, was held at the facilities of the Teaching and Research Workshop on Horticultural Plants (TEIPH), of the Faculty of Agronomy-UNAP, located at km 3 of the road to Zungarococha, south of the city of Iquitos. The type of research was experimental, explanatory with an independent variable (planting spacing) and seven dependent variables (plant height, plant diameter, fruit length, fruit diameter, fruit weight, number of fruits/plants, weight of fruits/plant, weight of fruits/ha). The objective of the research work was to determine the influence of planting spacing on the agronomic characteristics and yield of Capsicum annuum L. "pepper", Zungarococha-Loreto. 2019. The experimental design that was used was the Completely Random Block Design, with four treatments and four repetitions. Each experimental unit consisted of 2 rows, 6 plants/row and the sampling unit consisted of four plants/experimental unit. At the end of the experiment, the following conclusions were reached: The planting distance influences the Agronomic characteristics but not the yield of the Capsicum annuum L. "pepper" crop; the planting spacing with the greatest influence on the agronomic characteristics of Capsicum annuum L. "pepper" was that of Treatment T4 (0.80 m x 0.60 m); Treatment T4 (0.80 m x 0.60 m), presented the highest average yield value of fruit weight/ha, with 17,462.5 Kg; Treatment T4 (0.80 m x 0.60 m) obtained the best Cost/Benefit ratio, obtaining a utility of S/89,892.00.